Mining and Gender Gaps in India - Amanda Guimbeau; James Ji; Nidhiya Menon; Yana van der Meulen Rodgers (Institute of Labor Economics (IZA), 2020)
This study on the economics of gender differences examines whether the mining industry acts as a blessing or curse for women's well-being and economic status. The analysis focuses on the impact of proximity to mineral deposits and active mines on various measures of women's agency and health in India. Identification leverages the plausibly exogenous spatial variation in the occurrence of mineral deposits across districts. Results indicate that women's outcomes improve in the vicinity of mines with improvements in shared decision-making, reductions in barriers to accessing medical care, and reduced tolerance of physical violence. These benefits are pronounced among younger women, and in the proximity of mines that employ relatively high shares of women. The underlying mechanisms include employment gains for women and improvements in women's health near mines. Their children also experience gains in nutritional status. Men's likelihood of making decisions jointly with partners increases, and men are less likely to justify domestic violence. A key explanation for these results is the sharing of mining royalties with local groups that support investments in women and children. Findings imply that mineral mining can bring substantial benefits to women's well-being, which is critical for sustainable development.
Keywords: O13; Q32; J16; J12; 330; minerals; mining; women; agency; education; health; profit sharing; India